"Killed Out of Love": A Frame Analysis of Domestic Violence Coverage in Hong Kong. (October 2018) - Hernández, Miriam
A frame analysis was conducted on a Hong Kong newspaper to determine whether news coverage of female fatalities at the hands of their intimate partners was reported in conventional domestic violence ways or if there were culture-specific explanations. Overall, most coverage supported known views of domestic violence, justifying the perpetrator and categorizing the issue as isolated crime. However, a few stories highlighted the historical subordination of women under patriarchy in Confucianism as an important cultural factor. Findings have implications for the lack of generalization of the social problem, and the understanding of cultural and political power in Hong Kong society.